Small scale production system of broiler in Pabna and Sirajganj district of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The study was conducted in Pabna and Sirajganj districts under Rajshahi division of Bangladesh to assess the current scenario, feasibility, vaccination service, net income from small scale Broiler farming. The information was collected using pre-structured questionnaire from 50 randomly selected respondents who were involved in broiler farming. We collected the data related to family member(s), education, main occupation, training, annual income, number of broiler in each batch, name of feed Company; types of shed, existing marketing system etc. Results showed that out of 50 respondents 80% completed their graduation, 10% medium level of educated and rest of the respondents were illiterate. In case of farmer types, 29% small farmers, 41% medium type & rest of them were large type farmer. The day old chick (DOC) price was ranging from 40-42 taka each of all respondents. Most of the respondents used ready broiler feed and purchased from Kazi, Provita and Nourish Co.Ltd. About 30-40 % farmers marketed their birds at 32-35 days and final weight was ranging from 2.06- 2.29 kg/bird. The result of present study could be considered as a useful tool to new entrepreneurs at decision making in broiler production in Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 97-101